EVALUATION OF TEMEPHOS AS A POTENTIAL LARVICIDE AGAINST IMMATURE STAGES OF AEDES AEGYPTI (LINNAEUS) (DIPTERA: CULICIDAE) - Muhammad Sohail Qadir; Faisal Hafeez; Dilbar Hussain; Waseem Akram; Ayesha Iftikhar; Muhammad Saleem; Usama Saleem (Journal of Animal and Plant Sciences, 2025)
Aedes aegypti, a significant public health pest requires consistent insecticidal applications for effective management. Current laboratory study assessed the residual efficacy of two formulations of temephos—i.e., temephos 1G (granular) and temephos 50EC (liquid) against immature stages of Ae. aegypti focusing on survival and developmental plasticity. Survivors displayed prolonged developmental periods, with maturation durations of 12 days for temephos 1G, 22 days for temephos 50EC, and 30 days for the combined treatment (temephos 1G + temephos 50EC), compared to less than 6 days in the control group. Additionally, incomplete metamorphosis, including failed pupation and the inability to emerge as adults were observed. The combined treatment led to more pronounced reductions in fecundity, longevity, and egg viability compared to alone formulation.With the following survival durations: combination treatment (54 days), temephos 50EC (44 days), temephos 1G (32 days) and control (22 days), the survivorship curve demonstrated the impact of temephos on the larval population. Treated populations exhibited notable growth and developmental abnormalities. Although Ae. aegypti had lower mortality rates, their overall fitness was reduced, indicating a potential long-term decline in population.
Keywords: Temephos; Residual efficacy; Vector control; mosquito management; larval control